Pengembalian Barang Hutangan dengan Format Gotong Royong dalam Pembangunan Rumah - Ach. Fadlail; Nur Hasana (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2019)
Islam has taught all aspects of life, both of ritual worship and muamalah, worship which is needed to maintain the strength and harmony of human relations as servants with to Allah, while muamalah is said to be rulers of the game. It is one of the noble cultures of the Indonesian people which is always inherited and continues to be preserved from generation to generation until now, from this togetherness a tradition emerges in some societies known as "building materials". This custom has become a rooted tradition in the midst of community life including in Sumberejo Village, Banyuputih District, Situbondo Regency. Based on the results of this study, it can be seen that the practice of returning debts with the format of mutual cooperation in the construction of houses of them that are practiced in the form of debt-receivable transactions. Practices like this in fiqh are known as Qardh. The view of Islamic law on the practice of debt-debts with the format of legal cooperation because it has been based on the basis of mutual willingness and the existence of benefits that return to both parties.